Comparison of Target Detection Rates of Broad Multiplex Gastrointestinal PCR Panels to Inform Utilization of a Midplex Panel Approach: A Systematic Literature Review and Meta-Analysis - Jordan Chase; Darsh Devani; Bridget Manning; Anita Mohandas; Lucas Schulz; Thomas F Goss; D Jane Hata; Ping Ren (The Journal of Applied Laboratory Medicine, 2026)
Abstract Background Multiplex gastrointestinal panels (GIPs) allow rapid detection of infectious gastroenteritis pathogens. Broader 15- or 22-target (15t and 22t, respectively) panels also detect colonizing or nonetiologic organisms, increasing diagnostic uncertainty. We performed a systematic literature review and meta-analysis to estimate relative detection frequency (RDF) with an 11-target (11t) GIP compared with larger panels. Methods We searched PubMed and EMBASE (January 1, 2010–October 31, 2024) for studies reporting target-specific positivity in patients suspected of infectious gastroenteritis using 15t and 22t GIPs. Pooled detection rates were estimated via random-effects meta-analysis. Estimated RDF for the 11t panel was modeled using pooled target-specific positivity rates from 15t and 22t panels. RDF co-detection–adjusted positivity for the 11t panel was compared with the 15t and 22t GIPs. Twenty-five studies were included: 18 and 8 evaluating the 22t and 15t GIPs, respectively (one study included both). Results Adjusted pooled detection frequency rates were 32.94% (15t) and 50.01% (22t). Adjusted for co-detection, the 11t panel captured 57.3% of targets relative to 15t GIPs and 39.7% relative to 22t GIPs. The targets excluded from the 11t panel included Clostridioides difficile and certain Escherichia coli strains frequently identified in broader GIPs due to colonization. Larger multiplex GIPs yield more frequent positive results, offset by detecting organisms of questionable significance in asymptomatic patients or without risk factors. Conclusions Modeled findings suggest that an 11t panel preserves a clinically meaningful diagnostic yield while reducing co-detections, aligning with Infectious Diseases Society of America and American Society for Microbiology recommendations favoring targeted testing to improve diagnostic stewardship.